2019
DOI: 10.6008/cbpc2179-6858.2019.005.0027
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento pré-germinativo de sementes de cebolinha com peróxido de hidrogênio

Abstract: Objetivou-se estudar o tratamento pré-germinativo de sementes de cebolinha com diferentes concentrações de peróxido de hidrogênio. O experimento foi conduzido no laboratório de fisiologia vegetal pertencente à Universidade Federal de Campina Grande (UFCG). Os tratamentos foram distribuídos em delineamento inteiramente casualizado simples com cinco concentrações de peróxido de hidrogênio (0,0; 0,015; 0,030; 0,045 e 0,060 mM) e quatro repetições, totalizando 20 unidades experimentais. As sementes foram embebidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…The seed germination percentage of chives treated with hydrogen peroxide remained in accordance with the recommendation of the seed manufacturer, i.e., higher than 80%. It is noteworthy that, in the treatments with hydrogen peroxide application, there was faster germination and high uniformity, thus reaffirming the data of Santos et al [23], who obtained 81% germination percentage for chives using the same cultivar and treatments used as in this study.…”
Section: Sources Ofsupporting
confidence: 92%
See 1 more Smart Citation
“…The seed germination percentage of chives treated with hydrogen peroxide remained in accordance with the recommendation of the seed manufacturer, i.e., higher than 80%. It is noteworthy that, in the treatments with hydrogen peroxide application, there was faster germination and high uniformity, thus reaffirming the data of Santos et al [23], who obtained 81% germination percentage for chives using the same cultivar and treatments used as in this study.…”
Section: Sources Ofsupporting
confidence: 92%
“…It is noteworthy that, in the treatments with hydrogen peroxide application, there was faster germination and high uniformity, thus reaffirming the data of Santos et al [23], who obtained 81% germination percentage for chives using the same cultivar and treatments used as in this study.…”
Section: Sources Ofsupporting
confidence: 92%
“…The analysis of variance revealed a significant effect of the water salinity levels on the contents of modifications, constituting a 'stress memory' that can be expressed during other plant development phases (Santos et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…For the methods of application M1 and M3, exposure to H 2 O 2 started with the hydration of the seeds. Thus, several processes are initiated in the imbibed seeds, which can be stored as a kind of "stress memory" and can be expressed during later stages of plant development (Santos et al, 2019;Veloso et al, 2021). Furthermore, H 2 O 2 acts by interacting with hormones that control germination and production of O 2 for respiration in mitochondria, improving metabolic activity, besides helping to overcome seed coat dormancy, which in turn allows greater water absorption (Ahmad et al, 2013) and consequently may favor RDM production.…”
Section: /11mentioning
confidence: 99%
“…In this context, the exogenous application of hydrogen peroxide (H 2 O 2 ) constitutes an alternative to reduce the problems resulting from excess of salts (Silva et al, 2024) and may induce the acclimatization of plants. Santos et al (2019), working with H 2 O 2 , found that its use favored the growth of plants that were under salt stress.…”
Section: Introductionmentioning
confidence: 99%